BJOG Editor's Choice. (August 2016) - Thorp, John
Abstract : Deputy Editor‐in‐Chief, Professor John M Thorp, discusses his top articles from this issue in an audio podcast available at:https://soundcloud.com/bjog/august-editors-choice-2016 .